A autonomia da escola pública :um complexo movimento entre a outorga e a construção - Sousa, Luis Carlos Marques (2006)
The present research to explorer the configurations that come being given to the autonomy of the school, since the decade of 1990. We investigate the implementation of the principle of the autonomy in the public system of education of the State of Pernambuco and, specifically, in four school units and this schools its in the quarters of Stubborn Brasilia Teimosa and Casa Amarela, both located in Recife. We try to know if the implementation of the autonomy of the school is circumscribed in the process of productive reorganization, it was evidenced that the inclusion of this principle in the educational politics - in the scopes national and state - obeyed the dynamics of retraction that, in the neoliberal context, the performance of the State in relation to the public education and the school characterizes, with consequence impact in the investigated schools. From the empirical inquiry it was identified to the occurrence of a movement realized for the social actors of the schools research in direction to the construction of the pertaining to school autonomy; this movement presenting some limits and fragilities. It was evidenced despite this movement varied of intensity in the measure where the social actors of the schools had developed levels of dinamics processes (in greater or minor degree) related with the diverse expressions of democratic management that can occur into the school, such as: elaboration of the Politician-Pedagogical Project, institution and functioning of the Pertaining to school Advice, etc. The set of the carried through analyses made possible that it concluded that, in the context neoliberal and delimited to the investigated time and space, the implementation of the autonomy of the school comes if giving in way to a complex movement of construction